Psychosis secondary to indomethacin. A case report - González, S. Santiago; Sánchez-Lafuente, C. Gómez; Rico, A. Martinez; Molina, J. Hurtado (European psychiatry, 2021)
IntroductionIndomethacin, a non-steroidal anti-inflammatory treatment used in various inflammatory diseases, is one of the drugs that has been related to the appearance of psychotic symptoms as a side effect.ObjectivesPoint out the importance of knowing the possible psychiatric symptoms that some drugs can cause as a side effect.MethodsDescription of a clinical case and bibliography review.ResultsWe present the case of a 71-year-old woman, with no previous mental health history, who is referred by her primary care physician due to the presence of auditory hallucinations and self-referential ideas. As a somatic history, the patient presented Rheumatoid Arthritis under control by rheumatology and acoustic neuroma, under control by neurosurgery. Treatment with Risperidone was started, up to 2 mg, which helped control her symptoms. After an exhaustive study of her situation, the possibility that her symptoms were a side effect of her usual treatment was raised. It was evidenced that the patient had taken a higher dose of Indomethacin than prescribed by the rheumatologist, reason why its daily intake was suspended, and subsequently an improvement and even suppression of symptoms was seen. Later, due to a misunderstanding, the drug was reintroduced, and symptoms appeared again.ConclusionsThe appearance of psychotic symptoms has been related to the intake of various drugs, including Indomethacin. It is essential to carry out a differential diagnosis if psychotic symptoms appear in the subject.DisclosureNo significant relationships.